Congenital pulmonary airway malformation: advances and controversies. (April 2018) - Wong, Kenneth K Y; Flake, Alan W; Tibboel, Dick; Rottier, Robbert J; Tam, Paul K H
Summary: Advances in antenatal screening have provided evidence that the prevalence of congenital pulmonary airway malformation is higher than previously thought. This means that, on a global scale, more congenital pulmonary airway malformations will be diagnosed and seen by clinicians across many different specialties. This increase poses new controversies and challenges for clinicians in terms of prenatal and postnatal management. Important and exciting research has begun to emerge in the past decade. This Review describes current understanding of the disease, the latest surgical developments, and highlights management issues and controversies, including the rationale and timing of surgical intervention, the choice of surgical approach, and long-term functional outcomes. In doing so, we attempt to provide a balanced management algorithm for readers.